Dynamic response of density-graded foam subjected to soft impact - Liu, Hu (2022)
The density-graded foam materials are gaining traction due to their enhanced impact and blast resistance capacities. However, current knowledge in the impact response of density-graded foam is limited to rigid impact, which narrows the design space of target materials. In particular, three main issues remain unclear, i.e., (1) how to quantify soft impact response, (2) what is the reduction of deformation and transferred stress from soft impact as compared to rigid impact, (3) whether density-graded foam can reduce the transferred stress from soft impact. To address these knowledge gaps, an analytical model based on the double shock wave theory is established by using a deformable projectile impinging onto a density-graded foam target. The dynamic stress at the supported end is analyzed for uniform, positive, and negative density gradients. The results indicate that the deformation process due to impact from deformable projectile is vastly different from that of traditional rigid projectile, with the former causing 27.42% smaller deformation and 9.87% stress reduction of the graded foam target, and three separate velocities can be observed throughout the soft impact process. The findings indicate lower mechanical requirements of target materials for soft projectile impact protections, potentially leading to weight and cost savings.